Prebiotics Properties of Oolong Tea - Alfi Nur Rochmah; Choiriyah, Nurul Azizah; Abdi, Yenny Febriana Ramadhan; Widyastuti, Retno (Journal of Food and Agricultural Product, 2025)
Oolong tea is a semi-fermented tea derived from Camellia sinensis leaves. Oolong tea contains high polyphenol compounds that act as antioxidants and prebiotics. However, studies related to the prebiotic properties of oolong tea are still limited. This review aims to discuss scientific research that supports the concept of oolong tea polyphenol compounds as prebiotics. Oolong tea polyphenol compounds have low bioavailability. The part of the polyphenols that are not absorbed by the small intestine will be metabolized by intestinal bacteria. This has implications for improving intestinal microbiota and increasing SCFA production which have health effects on the body as antiobesity, improving colon inflammation and preventing cardiovascular disease. Keywords: Oolong tea, prebiotics properties